Strategic Management: Text And Cases - G.T Lumpkin (Mc Graw Hill, 2007)
Strategic Management: Text and Cases, 3rd Edition, by Dess/Lumpkin/Eisner is both readable and rigorous- written for today's student. A rocket-ship in its first editions, this revision continues to provide solid treatment of traditional topics in strategic management, as well as contemporary topics like entrepreneurship, innovation, knowledge management, and internet strategies. The prestigious author team understands the importance of thorough, modern concepts illustrated by rich, relevant, and teachable cases. The new case selections emphasize variety, currency, and familiar company names. The cases are up-to-date in terms of both financial data and strategic issues. This group of cases gives both instructors and students unparalleled quality and variety. Based on consistent reviewer feedback, these selections combine comprehensive and shorter length cases about well known companies.